"NICE" GRAMMARIANS: MAKING DISTINCTIONS OF CLASS, CHARACTER AND GENDER IN WOMEN'S FICTION, 1750–1830. Issue 1 (2nd January 2016) - Percy, Carol
ABSTRACT: For one of its reviewers, The Accidence; or First Rudiments of English Grammar. Designed for the Use of Young Ladies [ … ] By a Lady (1775) epitomized contemporary developments in both women's writing and vernacular grammar. In this article, the author summarizes the imaginative impact of this growing interest in English grammar by surveying the fiction published by women (1750–1830) that is available through Literature Online . Both grammar and fiction have general connections with the socio-economic uncertainty that was stereotypical of the long eighteenth century. Normative grammar rules complemented socio-economic mobility (whether upward or downward), since language conventionally signals its user's social place. Fiction typically focused on the unmarried girl, a figure of intense social liminality. For women novelists (and others), grammar was a polysemous word and a complex concept, especially once it could refer to the vernacular as well as to Latin. In this article, the author demonstrates that (at least for well-educated girls) grammar was much more than an instrument of social discrimination. As a central element of polite education, grammar could represent the interactions of culture on nature, producing the categories of disciplined character and even gender—for girls and for boys, grammar was what distinguished, and thus separated, the sexes. But the representation of lovers' shared grammatical practice not only resolved courtship plots, but could also question social divisions and conventions. Indeed, grammar involves both women's and fiction's concerns—the interplay of culture and nature in individual development, and thus the difficulty and the importance of making distinctions.